2015
DOI: 10.1016/j.cose.2015.04.002
|View full text |Cite
|
Sign up to set email alerts
|

BankSealer: A decision support system for online banking fraud analysis and investigation

Abstract: good results, a leading Italian bank deployed a version of BankSealer in their environment to analyze frauds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 10 publications
3
53
0
1
Order By: Relevance
“…While the experiments presented in [8] showed that Banksealer is an effective approach in identifying frauds and seems to provide a meaningful support to the banking analysts in fraud investigation, one of its main limitations is the lack of a bi-directional communication channel between the unsupervised system and the banking analyst to collect and exploit analyst's feedback and knowledge to improve detection performance. Furthermore, Banksealer works with an empirical configurations of weights, manually set by analysts.…”
Section: Research Goalmentioning
confidence: 99%
See 3 more Smart Citations
“…While the experiments presented in [8] showed that Banksealer is an effective approach in identifying frauds and seems to provide a meaningful support to the banking analysts in fraud investigation, one of its main limitations is the lack of a bi-directional communication channel between the unsupervised system and the banking analyst to collect and exploit analyst's feedback and knowledge to improve detection performance. Furthermore, Banksealer works with an empirical configurations of weights, manually set by analysts.…”
Section: Research Goalmentioning
confidence: 99%
“…Therefore, as already successfully done in [7,8], we inject fraud scenarios that replicate the typical attacks performed against online banking users. We consider two types of fraudulent attacks, reconstructed using domain expert and analyst advice:…”
Section: Synthetic Fraud Scenariosmentioning
confidence: 99%
See 2 more Smart Citations
“…Carminati [5] suggested the BANKSEALER system which is a decision support system for analyzing online banking fraud. During the training phase of this system, easy models were developed to understand spending habits of customers based on past transactions.…”
Section: Introductionmentioning
confidence: 99%